The examination of teachers’ levels of organizational happiness - Vatansever Bayraktar, Hatice; Girgin, Sinan; Bayraktar, Hatice Vatansever (Canadian Center of Science and Education, 2020)
This study aims to investigate the levels of organizational happiness of teachers working in primary, secondary, and high schools and to determine whether there is a significant difference in terms of some demographic characteristics. The screening model was employed in the study. The study population consists of teachers working in the Küçükçekmece, Bağcılar, Avcılar, and Esenyurt districts during the 2017−2018 academic year. The sample of the study comprises 297 teachers working in the Küçükçekmece, Bağcılar, Avcılar, and Esenyurt districts and selected via the convenience/incidental sampling method. In the study, the “Personal Information Form” created by the researchers and the “School Happiness Scale” developed by Bulut (2015) were used as data collection tools. The SPSS packaged software was used in the data analysis. According to the results of the data analysis, teachers’ general happiness perceptions and organizational happiness perceptions were observed to be high according to the subdimensions of management processes, attitudes towards the teaching profession, communication, commitment and economic provision of the School Happiness Scale. Teachers’ perceptions of organizational happiness differed significantly according to the level of education taught by teachers in the subdimensions of management processes and economic provision of the School Happiness Scale. Teachers’ perceptions of organizational happiness differed significantly according to professional seniority in the management processes subdimension of the School Happiness Scale. Teachers’ perceptions of organizational happiness differed significantly in the subdimensions of management processes, attitudes towards the teaching profession, commitment, and economic provision of the School Happiness Scale and according to the branch variable in the overall total. Teachers’ perceptions of organizational happiness did not differ significantly according to the variables of gender, educational status, age, and seniority in the school where they worked.
Keywords: Teacher; Organizational happiness; Level of happiness